PERANCANGAN KATALOG JJ DETAIL BOUTIQUE JL. JUANDA NO.71B PADANG - HARRID EL BARRY, Drs. Ir. Heldi, M.Si., Ph.D., Dra. Jurpiani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
JJ Detail Boutique is located at JL. Juanda no.71B besides Pool Bus NPM Lolong Padang. JJ Detail Boutique carries a business in the field of fashion, especially women with casual themes in the city of Padang. Consumers don’t know and understand the superiority of JJ Details Boutique products and the optimal media available at boutiques now makes JJ Detail Boutique experience a decline in turnover. The purpose of catalog design as print media that serves to inform product information an informative and communicative manner for customer satisfaction to increase JJ sales turn over Boutique Details.The Catalog Design Method combines the intuitive BlackBox thinking method and GlassBox rational thinking method that has been prepared regularly to collect descriptive and qualitative data. Analysis of the approach in data collection, namely SWOT analysis, is obtained through collecting observation data and documentation directly to boutique locations. The main media catalog and design of this layout adapted to the clothing motif for the current boutique edition. Supporting media in the form of poster , invoices,business cards, member cards,stickers,paper bag and video.It is expected that the design of this catalog can contribute to increasing sales turnover, strengthing competitives for competitor of clothing boutique that have developed at this time.Keywords:JJ Boutique Details, Catalog, Informative, Communicative, Products.